1998
DOI: 10.1183/09031936.98.12061450
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personal tobacco smoking on the clinical practice of Italian chest physicians

Abstract: Tobacco smoking (TS) is a major cause of lung diseases. This study aimed to determine: 1) the prevalence of TS among chest physicians; 2) the influence of the personal smoking habit on clinical practice; and 3) what training about tobacco-related issues (TI) doctors received in medical school. A total of 983 attendees at the National Meeting of the Italian National Thoracic Society (AIPO) received a questionnaire about TI, which also contained the Fagerstroem Tolerance Questionnaire, and 605 (61.5%) answered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
8

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 7 publications
4
42
0
8
Order By: Relevance
“…taking a crystal from the same batch, also showed electron density for a chloride ion in this position (Nardini, 1998). Thus, the presence of the ion is more likely to arise from the crystallization medium or the PEG 6000 in the cryoprotectant solution, which might have contained traces of chloride.…”
Section: Chloride Bindingmentioning
confidence: 91%
“…taking a crystal from the same batch, also showed electron density for a chloride ion in this position (Nardini, 1998). Thus, the presence of the ion is more likely to arise from the crystallization medium or the PEG 6000 in the cryoprotectant solution, which might have contained traces of chloride.…”
Section: Chloride Bindingmentioning
confidence: 91%
“…Tütün ürünü tüketmeyen hekimler çalıştıkları yerleri de hastalarını da olumlu bir örnek oluşturarak etkiledikleri gibi, tüketen hekimlere göre tütün ürünleri-nin olumsuz etkilerini daha fazla önemsemekte ve bu konuda hekim rolüne daha fazla inanarak hastalarına daha güçlü destek sunmaktadırlar (6,7) .…”
Section: Tütün üRünü Kullanmayan Tutum Sergileyerek Olumlu öRnek Oluşunclassified
“…In 2012, more than a quarter of the population of 15 to 64 years was a tobacco consumer [4][5][6][7][8][9][10][11][12]. The majority of Portuguese started smoking consumption between 12 and 20 years of age, largely due to the influence of friends or curiosity and willingness to experiment.that it is imperative to invest in prevention and control of this important national public health problem [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that as smoking rates decline among physicians, a similar reduction will be observed in the general population as well. Recent data demonstrated that surgical specialities have greater tendency to stress with more highest percentage of smokers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%